Labrador, aerial view of Torngat Mountains with Ungava Bay in extreme background - Forbes, Alexander, 1882-1965 (1931)
(Series 26) Semicircular inland flight from Ryan's Bay southwest to the Central Range, then southeast along it to Komaktorvik Lake, then northeast to Tetragona. Camera facing right front to line of flight. Fig. 81 - Northern end of the interior range of the Torngat Mountains looking northwest to the shore of Ungava Bay in the background. Cirque cutting has notched the border of an older erosion surface that fills the left foreground. Compare with Figure 65. Aug. 3, 1931. Forbes, A., Miller, O. M., Odell, N. E., & Abbe, E. C. (1938). Northernmost Labrador mapped from the air. New York: American Geographical Society. Grayscale